Safety of "hot" and "cold" site admissions within a high‐volume urology department in the United Kingdom at the peak of the COVID‐19 pandemic. Issue 2 (21st January 2021) - Stroman, Luke; Russell, Beth; Kotecha, Pinky; Kantartzi, Anastasia; Ribeiro, Luis; Jackson, Bethany; Ismaylov, Vugar; Debo‐Aina, Adeoye Oluwakanyinsola; MacAskill, Findlay; Kum, Francesca; Kulkarni, Meghana; Sandher, Raveen; et al.
Abstract: Objectives: To determine the safety of urological admissions and procedures during the height of the COVID‐19 pandemic using "hot" and "cold" sites. The secondary objective is to determine risk factors of contracting COVID‐19 within our cohort. Patients and methods: A retrospective cohort study of all consecutive patients admitted from March 1 to May 31, 2020 at a high‐volume tertiary urology department in London, United Kingdom. Elective surgery was carried out at a "cold" site requiring a negative COVID‐19 swab 72‐hours prior to admission and patients were required to self‐isolate for 14‐days preoperatively, while all acute admissions were admitted to the "hot" site. Complications related to COVID‐19 were presented as percentages. Risk factors for developing COVID‐19 infection were determined using multivariate logistic regression analysis. Results: A total of 611 patients, 451 (73.8%) male and 160 (26.2%) female, with a median age of 57 (interquartile range 44‐70) were admitted under the urology team; 101 (16.5%) on the "cold" site and 510 (83.5%) on the "hot" site. Procedures were performed in 495 patients of which eight (1.6%) contracted COVID‐19 postoperatively with one (0.2%) postoperative mortality due to COVID‐19. Overall, COVID‐19 was detected in 20 (3.3%) patients with two (0.3%) deaths. Length of stay was associated with contracting COVID‐19 in our cohort (OR 1.25, 95% CI 1.13‐1.39). Conclusions: Continuation of urological procedures using "hot" and "cold" sites throughout the COVID‐19 pandemic was safe practice, although the risk of COVID‐19 remained and is underlined by a postoperative mortality.